Preparation and characterization of dye-sensitized solar cells - Kerh, Shu Li (2015)
This report records the preparation and characterisation process of a hybrid solid-state dye-sensitized solar cell (DSSC) using Indium Tin Oxide (ITO) glass, TiO2 nanoparticles, Cadmium Telluride (CdTe) quantum dots, Thieno[3,2-b]thiophene-2-carboxaldehyde organic dye, Poly (3-hexylthiopene-2,5-diyl) (P3HT) and Poly (3,4-ethylenedioxythiopene) Polystyrene Sulfonate (PEDOT: PSS). In this report, it mainly describes a number of variations, such as using different combination of photo-sensitizer concentration, made to each layer of the hybrid DSSC device so as to optimize photo–induced charge separation and electron transfer processes. The problems encountered on the limitation of various deposition techniques are highlighted while possible alternative solutions are suggested for further step improvisation. It also includes tables and graphs of the simulated results from the Keithley software using digital multi-meter, solar simulator and prober station. The analysis and discussion of the experimental results show that with increasing concentration of photo-sensitizer helps to improve optical absorption efficiency and generate larger short circuit current and open circuit voltage which is in line with the theoretical concepts.